Architecture, flexibility and performance of a special electron linac dedicated to Flash radiotherapy research: electronFlash with a triode gun of the centro pisano flash radiotherapy (CPFR) - Di Martino, F.; Del Sarto, D.; Bass, G.; Capaccioli, S.; Celentano, M.; Coves, D.; Douralis, A.; Marinelli, M.; Marrale, M.; Masturzo, L.; Milluzzo, G.; Montefiori, M.; et al. (Frontiers in Physics, 2023)
The FLASH effect is a radiobiological phenomenon that has garnered considerable interest in the clinical field. Pre-clinical experimental studies have highlighted its potential to reduce side effects on healthy tissues while maintaining isoeffectiveness on tumor tissues, thus widening the therapeutic window and enhancing the effectiveness of radiotherapy.The FLASH effect is achieved through the administration of the complete therapeutic radiation dose within a brief time frame, shorter than 200 milliseconds, and, therefore, utilizing remarkably high average dose rates above at least 40 Gy/s. Despite its potential in radiotherapy, the radiobiological mechanisms governing this effect and its quantitative relationship with temporal parameters of the radiation beam, such as dose-rate, dose-per-pulse, and average dose-rate within the pulse, remain inadequately elucidated. A more profound comprehension of these underlying mechanisms is imperative to optimize the clinical application and translation of the FLASH effect into routine practice.Due to the aforementioned factors, the undertaking of quantitative radiobiological investigations becomes imperative, necessitating the utilization of sophisticated and adaptable apparatus capable of generating radiation beams with exceedingly high dose-rates and dose-per-pulse characteristics. This study presents a comprehensive account of the design and operational capabilities of a Linear Accelerator (LINAC) explicitly tailored for FLASH radiotherapy research purposes. Termed the "ElectronFlash" (EF) LINAC, this specialized system employs a low-energy configuration (7 and 9 MeV) and incorporates a triode gun. The EF LINAC is currently operational at the Centro Pisano FLASH Radiotherapy (CPFR) facility located in Pisa, Italy.Lastly, this study presents specific instances exemplifying the LINAC's adaptability, enabling the execution of hitherto unprecedented experiments. By enabling independent variations of the temporal parameters of the radiation beam implicated in the FLASH effect, these experiments facilitate the acquisition of quantitative data concerning the effect's dependence on these specific parameters. This novel approach hopefully contributes to a more comprehensive understanding of the FLASH effect, shedding light on its intricate radiobiological behavior and offering valuable insights for optimizing its clinical implementation.